(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article provides a scientific and theoretical analysis of the mechanisms of interaction between the media space and social consciousness, the impact of modern information and communication technologies on the transformation of youth values, and the main trends and factors of this process. The study examines the impact of digital media, social networks and the virtual environment on the worldview, national value system and social behavior of Uzbek youth. Using content analysis, questionnaires and observation methods, the main directions of change in youth values were identified, conclusions of pedagogical and social significance were formulated, and practical recommendations were developed.